The Role of Computer-Mediated Language Learning in Promoting Vocabulary Development: An Applied Linguistics Study - Nurdin Nurdin; Darmawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Learning vocabulary is one of the basic parts of learning a language, especially for the learners with elementary English skills. This study investigates the role of Computer-Mediated Language Learning (CMLL) in promoting vocabulary development among first semester students in an English language learning setting. The study employs a qualitative research design to explore learners’ experiences, perceptions and engagement with technology-assisted vocabulary learning activities. There were 30 participants at first semester students with a beginner level of English proficiency. Data were collected by classroom observations, semi-structured interviews, and document analysis of students’ learning activities. The results suggest that Computer-Mediated Language Learning has a positive effect on vocabulary development, as it raises learners’ exposure to new lexical items, increases their awareness of pronunciation and encourages autonomous learning practices. Students used digital platforms, interactive applications, and multimedia resources to grasp word meanings, contextual usage.